Impresso, escola e ensino de História no estudo da coleção de livros Fundadores da América Latina - Lima, Aline De Sousa [UNIFESP] (2019)
This master's dissertation proposes a study on the teaching of History in Latin America, from the material reader of teaching American History, the collection Founders of Latin America. This collection of books was published in 2008 by the Memorial Foundation, the Education Development Fund (EDF) and by the SECRETARY OF EDUCATION OF THE STATE OF SÃO PAULO (SEE / SP), for the schools of the state public school system. The ´Founders of Latin America collection is composed of six volumes, in bilingual format, Portuguese and Spanish, designed as an initiative for the dissemination and knowledge of Latin American issues in the public schools of the state of São Paulo. Therefore, this study proposes to carry out an analysis of the pedagogical, political and editorial project of this publication in dialogue with the teaching of History, according to bibliography on the history of the book and the collections.